Solve for z b=1/3*(m(s+z)fors)

Math
b=13⋅(m(s+z)fors)
Rewrite the equation as 13⋅(m(s+z)fors)=b.
13⋅(m(s+z)fors)=b
Multiply both sides of the equation by 3.
3⋅13⋅(m(s+z)fors)=3⋅b
Simplify 3⋅13⋅(m(s+z)fors).
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3⋅13⋅(m(s+z)fors)=3⋅b
Rewrite the expression.
1⋅(m(s+z)fors)=3⋅b
1⋅(m(s+z)fors)=3⋅b
Multiply m(s+z)fors by 1.
m(s+z)fors=3⋅b
Apply the distributive property.
(ms+mz)fors=3⋅b
Apply the distributive property.
(msf+mzf)ors=3⋅b
Apply the distributive property.
(msfo+mzfo)rs=3⋅b
Apply the distributive property.
(msfor+mzfor)s=3⋅b
Apply the distributive property.
msfors+mzfors=3⋅b
Multiply s by s by adding the exponents.
Tap for more steps…
Move s.
m(s⋅s)for+mzfors=3⋅b
Multiply s by s.
ms2for+mzfors=3⋅b
ms2for+mzfors=3⋅b
ms2for+mzfors=3b
Subtract ms2for from both sides of the equation.
mzfors=3b-ms2for
Divide each term by mfors and simplify.
Tap for more steps…
Divide each term in mzfors=3b-ms2for by mfors.
mzforsmfors=3bmfors+-ms2formfors
Simplify mzforsmfors.
Tap for more steps…
Cancel the common factor of m.
Tap for more steps…
Cancel the common factor.
mzforsmfors=3bmfors+-ms2formfors
Rewrite the expression.
zforsfors=3bmfors+-ms2formfors
zforsfors=3bmfors+-ms2formfors
Cancel the common factor of f.
Tap for more steps…
Cancel the common factor.
zforsfors=3bmfors+-ms2formfors
Rewrite the expression.
zorsors=3bmfors+-ms2formfors
zorsors=3bmfors+-ms2formfors
Cancel the common factor of o.
Tap for more steps…
Cancel the common factor.
zorsors=3bmfors+-ms2formfors
Rewrite the expression.
zrsrs=3bmfors+-ms2formfors
zrsrs=3bmfors+-ms2formfors
Cancel the common factor of r.
Tap for more steps…
Cancel the common factor.
zrsrs=3bmfors+-ms2formfors
Rewrite the expression.
zss=3bmfors+-ms2formfors
zss=3bmfors+-ms2formfors
Cancel the common factor of s.
Tap for more steps…
Cancel the common factor.
zss=3bmfors+-ms2formfors
Divide z by 1.
z=3bmfors+-ms2formfors
z=3bmfors+-ms2formfors
z=3bmfors+-ms2formfors
Simplify each term.
Tap for more steps…
Cancel the common factor of m.
Tap for more steps…
Cancel the common factor.
z=3bmfors+-ms2formfors
Rewrite the expression.
z=3bmfors+-1s2forfors
z=3bmfors+-1s2forfors
Cancel the common factor of s2 and s.
Tap for more steps…
Factor s out of -1s2for.
z=3bmfors+s(-1sfor)fors
Cancel the common factors.
Tap for more steps…
Factor s out of fors.
z=3bmfors+s(-1sfor)s(for)
Cancel the common factor.
z=3bmfors+s(-1sfor)s(for)
Rewrite the expression.
z=3bmfors+-1sforfor
z=3bmfors+-1sforfor
z=3bmfors+-1sforfor
Cancel the common factor of f.
Tap for more steps…
Cancel the common factor.
z=3bmfors+-1sforfor
Rewrite the expression.
z=3bmfors+-1soror
z=3bmfors+-1soror
Cancel the common factor of o.
Tap for more steps…
Cancel the common factor.
z=3bmfors+-1soror
Rewrite the expression.
z=3bmfors+-1srr
z=3bmfors+-1srr
Cancel the common factor of r.
Tap for more steps…
Cancel the common factor.
z=3bmfors+-1srr
Divide -1s by 1.
z=3bmfors-1s
z=3bmfors-1s
Rewrite -1s as -s.
z=3bmfors-s
z=3bmfors-s
z=3bmfors-s
Solve for z b=1/3*(m(s+z)fors)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top